2021
DOI: 10.1021/acssynbio.0c00582
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Alternate Ligand Recognition in the PurR Topology: A System of Novel Caffeine Biosensing Transcriptional Antirepressors

Abstract: Recent advances in synthetic biology and protein engineering have increased the number of allosteric transcription factors used to regulate independent promoters. These developments represent an important increase in our biological computing capacity, which will enable us to construct more sophisticated genetic programs for a broad range of biological technologies. However, the majority of these transcription factors are represented by the repressor phenotype (BUFFER), and require layered inversion to confer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 101 publications
0
16
0
Order By: Relevance
“…To accomplish this, we leveraged the workflows that we developed in refs. 13 and 30 , which required an initial block in allosteric communication (i.e., via conferred superrepression S S YQR ) followed by one or more round(s) of error-prone PCR (EP-PCR). To identify putative superrepressor mutations, we performed a primary structure alignment between LacI and GalS ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To accomplish this, we leveraged the workflows that we developed in refs. 13 and 30 , which required an initial block in allosteric communication (i.e., via conferred superrepression S S YQR ) followed by one or more round(s) of error-prone PCR (EP-PCR). To identify putative superrepressor mutations, we performed a primary structure alignment between LacI and GalS ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Repressors are bound to DNA operators in the absence of the ligand, inhibiting transcription, and dissociate (are induced) when the ligand is present ( 21 , 23 ). The engineering of the transcriptional antirepressor (X A , where A indicates the antirepressor phenotype) has additionally resulted in increased computing capacity in synthetic biology ( 13 , 27 30 ). While repressors function as Boolean BUFFER gates ( 12 , 13 ), antirepressors function as Boolean NOT gates ( 13 , 25 , 30 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of natural proteins have been used in various combinations with engineered DNA operator sequences to create transcription “circuits” that respond in desired ways to varied effector ligands 1‐6 . In addition, the transcription factors have themselves been subjected to engineering via mutagenesis and/or domain recombination to achieve novel activities 7‐13 …”
Section: Figurementioning
confidence: 99%
“…Accordingly, several groups have demonstrated that functional chimeras can be constructed based on the given engineering principles. 29,33−37 Wilson et al, in a collection of studies, posited and demonstrated that modular design could be applied to engineered domains�i.e., alternate (engineered) DNA binding functions, 29,35 alternate (engineered) allosteric communication, 30,35,37,38 and alternate (engineered) ligand binding functions 36,37 �to create a system of transcription factors (repressors and antirepressors) that are network capable. To date, using this collection of engineered repressors and antirepressors, transcriptional programs are designed and constructed intuitively�though with an apparent rule set (see Supporting Note 4).…”
Section: ■ Introductionmentioning
confidence: 99%